Multiplex one-step RT–qPCR assays for simultaneous detection of BRV, BCoV, Escherichia coli K99+ and Cryptosporidium parvum - Zhao, Xinru; Li, Min; Yang, Yingying; Wang, Yidan; Zheng, Xiaoru; Yin, Dehua; Gao, Haihui; Li, Huatao; Fu, Kaiqiang; Cao, Zhi (Frontiers in Veterinary Science, 2025)
IntroductionBovine rotavirus (BRV), bovine coronavirus (BCoV), Escherichia coli K99+ (E. coli K99+), and Cryptosporidium parvum (C. parvum) are the most common pathogens involved in calf production. These pathogens can cause calf diarrhea, leading to significant economic losses in the cattle farming industry. These four pathogens have similar clinical symptoms, making them difficult to distinguish. Therefore, we established a one-step quadruple TaqMan fluorescence quantitative PCR method capable of simultaneously and rapidly detecting BRV, BCoV, E. coli K99+, and C. parvum.MethodsSpecific primers and TaqMan probes were designed for the BRV VP-6 gene, BCoV N gene, E. coli K99+ K99 gene, and C. parvum 18S rRNA gene. Standard positive plasmids were constructed, and the reaction conditions of the method were optimized. The sensitivity, specificity, and repeatability of the method were validated, and clinical samples were tested.ResultsThe minimum detection limits of this method for BRV, BCoV, E. coli K99+, and C. parvum were 5.8 × 101, 2.3 × 101, 4.5 × 102, and 2.6 × 101 copies/μL, respectively. The intra- and intergroup coefficients of variation were all less than 1.2%. This method has the advantages of strong specificity, reproducibility, low cost, and no cross-reaction with other bovine pathogens. Compared with the commercial reagent kit method were used to analyze clinical samples, and both the diagnostic sensitivity (DSe) and diagnostic specificity (DSp) were above 90%, with kappa values greater than 0.9.DiscussionThe one-step multiplex RT-qPCR method developed in this study for detecting BRV, BCoV, E. coli K99+, and C. parvum is expected to be an effective tool for the rapid and economical diagnosis and monitoring of diarrhoeal diseases in calves.